Methodology for the implementation of photovoltaic systems with storage for small industries - Gómez-Ramírez, Gustavo Adolfo (2022)
Today, small-scale non-conventional renewable generation systems are beginning to gain strength within electrical power systems. Generation for self-consumption can benefit small and medium-sized companies in order to make them more competitive and attractive to customers. Small-scale wind systems, as well as solar system installations, are an example of how technology has become widespread, so having an explicit, simple and reliable procedure for the implementation of renewable systems would be very useful. This article presents a step-by-step procedure about the implementation of photovoltaic systems in small industries where it proposes a design of an installation including an economic analysis. Energy storage systems are taken into account. The economic and environmental benefits are considerable, where a high viability of implementation of this type of applications in small industries is demonstrated. It was concluded that the implementation of a photovoltaic solar system in a small company allows reductions in electricity costs greater than 90% with a prompt recovery of the investment.